Analisis Kelayakan Pembiayaan Bank Syariah - Ilyas, Rahmat (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2019)
Sharia banks are banks that operate by not relying on interest. Islamic banks or commonly referred to as a bank without interest, is a financial institution / banking operational and its products are developed based on al-Qur'an and hadith. Financing is one of the principal tasks of banks, namely the provision of facilities to provide funds to meet the needs of the parties which is the unit deficit. The main purpose of the financing analysis is to gain confidence whether the customer has the willingness and ability to fulfill his obligations in an orderly manner, both principal and profit sharing in accordance with the agreement with the bank.